What is meat in Argentina? - Pavan, Enrique (2017)
Due to its strong cultural significance, the term “meat” in Argentina has been historically associated with beef, despite its wider definition in the Argentine Food Code. Only by the end of the last century did other meats (poultry and pork) start gaining participation in the Argentinean diet as a result of economic and health-related issues. Meat, in general, is recognized as an important source of high-value proteins by consumers and professionals but not as an important source of minerals and vitamins.